TUJUAN PENDIDIKAN ISLAM MENURUT PARA ULAMA SALAFI: (Shaikh ʾIbn Bāz, ʾAl-Albāniy dan Ibn ʾAl-ʿUthaimīn) - Oscar Wardhana Windro Saputro (STAI Ali bin Abi Thalib Surabaya, 2022)
This research aims to find out the educational thoughts of the salafis regarding the purpose of Islamic education. The salafi scholars who will be examined and compared regarding the objectives of Islamic education are Shaikh ʾIbn Bāz, Shaikh ʾAl-Albāniy and Shaikh ʾAl-ʿUthaimīn. Based on the place, type of data and source of research, this research is qualitative research and is categorized as library research. Data is collected from primary data sources in the form of written works and biographies and secondary data sources, namely supporting data sources in the form of articles, newspapers, magazines, journals, theses and books from other researchers related to research studies. After the research was conducted, the following findings were obtained: Shaikh ʾIbn Bāz views that the purpose of Islamic education is the wisdom of human creation itself, namely the monotheism of Allah, which is realized by offering worship only to Allah. Shaikh ʾAl-Albāniy emphasized that the purpose of education is tawheed, which is the foundation of Islam, namely worshiping only Allah, as practiced by the Messenger of Allah (peace and blessings of Allah be upon him) and his companions. Shaikh ʾAl-ʿUthaimīn implies that the purpose of Islamic education is the purpose of the creation of man himself by Allah, namely to monotheize Allah in worship only to Him. The purpose of Islamic education according to these three scholars is in accordance with the wisdom of the purpose of human creation, and in accordance with the da'wah of the prophets and messengers, including the Prophet Muhammad (peace and blessings of Allaah be upon him) and his companions, namely tawhidullah, to glorify only Allah in worship.